Whole mitochondrial genome sequencing in individuals with Leber hereditary optic neuropathy negative for the common pathogenic mitochondrial DNA variants - Srilekha, Sundaramurthy; Ambika, Selvakumar; Hemavathy, Nagarajan; Vidhya, Dharani; Yu-Wai-Man, Patrick (Frontiers in Neurology, 2025)
PurposeThis study aimed to explore the role of additional mitochondrial DNA (mtDNA) variants in the development of Leber hereditary optic neuropathy (LHON) by screening the entire mitochondrial genome in individuals who had previously tested negative for the three common mtDNA variants: m.3460G > A (MT-ND1), m.11778G > A (MT-ND4), and m.14484 T > C (MT-ND6), by conventional Sanger sequencing.MethodsForty-one individuals with a suspected clinical diagnosis of LHON were recruited from the neuro-ophthalmology clinic. Each participant had undergone a comprehensive neuro-ophthalmic examination, including slit lamp examination, indirect ophthalmoscopy, visual field perimetry, optical coherence tomography, and MRI of the brain and orbits. Targeted re-sequencing was conducted using next-generation sequencing (NGS) on the HiSeqX 10 platform (Illumina, San Diego, California) with a 2 × 150 bp paired-end configuration. The sequencing reads were aligned to the human mitochondrial genome sequence (hg19). Variants were filtered with the VariMAT tool (v.2.3.9). Haplogroup analysis was performed using Haplogrep 2 (v2.0). To assess the deleteriousness of nonsynonymous variations, bioinformatics prediction tools such as PolyPhen2, SIFT, CADD, and Mutation Assessor were utilized. In addition, while tools like Consurf, PredictSNP, DynaMut, ENCoM, DUET, SDM, mCSM, were employed to evaluate evolutionary conservation, pathogenicity, structural stability, and functional impact.ResultsWhole mitochondrial genome sequencing of 41 clinically suspected LHON cases identified a total of 1,518 mtDNA variants. Of these, 822 were located in the coding regions, including 555 synonymous and 273 non-synonymous variants. Two heteroplasmic disease-causing variants (m.11778G > A and m.3460G > A) were identified in one individual each (90.0 and 63.6%, respectively). Additionally, rare mtDNA variants listed in Mitomap were found in five individuals (5/41, 12.1%), namely, MT-ND1 (m.3335 T > C, m.3394 T > C, m.3395A > G), MT-ND4L (m.10680G > A), and MT-ND6 (m.14502 T > C), with variants in MT-ND1 being the most prevalent (3/41, 7.3%).ConclusionOur study of a well-characterized Indian LHON cohort uncovered rare mtDNA variants that should be considered when assessing undiagnosed optic neuropathy cases. Additionally, it underscores the effectiveness of NGS in identifying heteroplasmic mtDNA variants. This indicates that whole mitochondrial genome sequencing via NGS is a more efficient and preferred approach for routine molecular genetic testing.